Anatomical study in the Western world before the Middle Ages: historical evidence - Conti, Andrea Alberto; Paternostro, Ferdinando (Acta Biomedica Atenei Parmensis, 2019)
Although modern anatomy is commonly retained to begin in the XVI century, the roots of anatomical study in the Western world may be identified beforehand. An anatomical practice was present in the Western world well before the Middle Ages, starting in ancient Greece. Hippocrates of Cos (V-IV centuries B.C.) provided descriptions of the heart and vessels, and the so-called “Hippocratic Corpus” largely deals with anatomy. Aristotle of Stagira (IV century B.C.) was one of the first well-known scholars of the past to perform dissections of animals. The anatomical interest of Aristotle contained a “physiological” background too, since he was convinced that all parts of human organisms had one or more specific functions. Galen of Pergamum (II century A.D.) was the performer of hundreds of dissections of animals, and he described a great number of anatomical parts of apes, dogs, goats and pigs. The anatomical system of Galen became a gold standard for medicine for more than a thousand years, and in the Middle Ages (V-XV centuries A.D.) the human anatomy that was taught and acquired in European universities remained based on Galenic anatomy. In conclusion, Greek-speaking scholars between the IV century B.C. and the II century A.D. set the basis for the systematic dissection of animals and the comparative investigation of animal anatomical findings. These scholars also began to study the structures of the human body, interestingly taking into account the relationship between the macroscopical morphology of observed structures and their more evident functions. (www.actabiomedica.it)